Order of discontinuation of glucose-lowering medications following bariatric surgery. (February 2021) - Vouri, Scott Martin; Chen, Jiajing; Sparkman, Jayme; Salles, Arghavan; Micek, Scott T
Highlights: 98% of patients on ≥2 glucose-lowering medications (GLMs) stopped ≥1at least one GLM. Heterogeneity in the order of GLM discontinuation after bariatric surgery existed. Correlation between lack of GLM discontinuation and hypoglycemia warrants study. Abstract: Aims: To assess the order of glucose-lowering medication (GLM) discontinuation following bariatric surgery among patients taking ≥2 GLMs. Methods: Patients with diabetes mellitus taking ≥2 GLM classes who underwent bariatric surgery were identified using health claims data from the United States. The order of discontinuation was assessed in patients taking ≥2 GLM classes by comparing each GLM class to the other classes in aggregate. Descriptive statistics and Poisson regression were used to assess the order of discontinuation and changes in trends in the order of discontinuation. Results: Overall, 12, 244 of 26, 651 patients with type 2 diabetes who underwent bariatric surgery were taking ≥2 GLM classes. When each GLM class was assessed separately, fewer than 50% of patients had metformin, sulfonylurea, thiazolidinedione, DPP-4 inhibitor, SGLT2 inhibitor, glucosidase inhibitor, or insulin discontinued first when compared to the other classes in aggregate. Between 2008 and 2014, thiazolidinediones were increasingly more likely to be the first GLM discontinued (p = 0.0432). Slightly more than 50% of patients whose GLM regimen included a sulfonylurea discontinued the sulfonylurea first despite clinical recommendations. Conclusions: From a population level, there was no consistent approach in the order of discontinuation of GLM classes in patients following bariatric surgery.